Pengaruh Gaya Kepemimpinan Transformasional dan Komitmen Organisasional terhadap Prestasi Kerja Pegawai pada PDAM Tirta Khatulistiwa Pontianak - Daud, Ilzar; Afifah, Nur (Fakultas Ekonomi dan Bisnis, UNTAN, 2019)
This study aims to determine how the influence of transformational leadership style and organizational commitment on job performance at PDAM Tirta Khatulistiwa Pontianak. Population in this research is employees at PDAM Tirta Khatulistiwa Pontianak Service Department as many as 120 employees and sampling research as many as 51 respondents or 43% of the population. The sampling technique uses purposive sampling. The questionnaires used for transformational leadership style variables are Multifactor Leadership Questionnaire (MLQ), for organizational commitment variables using Organizational Commitment Questionnaire (OCQ), and job performance variables using job performance questionnaires. The analytical technique used is the multiple linear regression analysis. The result of the research shows that the simultant transformational leadership style and organizational commitment have a significant effect on the job performance and partially, both the transformational leadership style and organizational commitment have a significant effect on the job performance of PDAM Tirta Khatulistiwa Pontianak.